Tough Boris - Fox, Mem, 1946-; Brown, Kathryn, 1955- (San Diego : Harcourt Brace, 1998)
Although he is a very tough pirate, Boris von der Borch cries when his parrot dies.
School Library Journal
Booklist
Horn Book Magazine
2.2
K-3
Keywords: Pirates -- Fiction; Pirates -- Fiction